Large-scale Android malware detection by integrating Blockchain and IPFS for secure virus signature distribution - Cam, Nguyen Tan; Duy, Pham Nhat; Phuc, Hoang Mai Thien (Journal of Science and Technology on Information security, 2025)
The growing threat of Android malware underscores the limitations of centralized antivirus systems, which face challenges such as latency, single points of failure, and susceptibility to attacks. To address these issues, this paper introduces a decentralized framework leveraging blockchain technology via Hyperledger Fabric and the InterPlanetary File System (IPFS). The system, HypatiaX, provides secure, efficient, and transparent virus signature distribution while ensuring scalable and resilient data storage. By utilizing blockchain for virus signature management and IPFS for decentralized storage, HypatiaX supports real-time updates in distributed environment. Performance evaluations reveal low resource consumption, near-instantaneous query responses, and efficient virus scanning under diverse conditions. Advanced components, including a ledger controller, signature crawler, key manager, and IPFS client, further strengthen decentralized storage, secure key management, and automatic signature updates. This framework demonstrates significant improvements in combating Android malware while addressing the inherent flaws of traditional antivirus solutions.